PLAYING THE SECOND FIDDLE - THE EXPERIENCES, CHALLENGES AND COPING STRATEGIES OF CONCERNED SIGNIFICANT OTHERS OF PARTNERS WITH A SUBSTANCE USE DISORDER: INFORMING SOCIAL WORK INTERVENTIONS - Schultz, Peter; Alpaslan, Assim Hassim (Social Work/Maatskaplike Werk, 2020)
Substance abuse constantly wreaks havoc on families. A family member’s substance use disorder (SUD) repeatedly turns a home into a volatile, toxic environment, immersing concerned significant others (CSOs) in a state of confusion and hardship, forcing them to sacrifice their own energies and resources in order to manage this aberration in their midst, often to the extent that they eventually adopt maladaptive behaviours themselves to survive. When partners with an SUD enter treatment, the interventions primarily focus on them, while the non-abusing CSO partner is regarded as an adjunct to the primary treatment and instrumental in a successful treatment outcome. The CSO’s own needs usually go unrecognized and they seldom receive specialised treatment to recover from the anguish caused by a partner’s SUD, depriving them of a service they are entitled to as individuals in their own right. This phenomenon explains the lacuna in treatment regimens aimed at CSOs which should also fall within the ambit of social work.